Pengaruh Biaya Operasional (BOPO) Dan Non-Performing Loan (NPL) Terhadap Return Of Asset (ROA) Pada Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2020-2024 - Pujiyanti Pujiyanti; Sinta Amalia; Nafsa Qolbina Istigfari; Sri Yulandasari Lajai; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the effect of BOPO and NPL on Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The data were processed using EViews 12 through panel data regression, which included data preparation, descriptive statistics, normality testing, panel-specific diagnostic tests, and model selection using the Chow, Hausman, and LM tests. The results indicate that the Random Effect Model (REM) is the most appropriate model for this research. The findings show that BOPO has a negative and significant effect on ROA, while NPL has a negative but insignificant effect. Simultaneously, both variables significantly influence ROA, with an R² of 93.03%, indicating strong explanatory power. The study concludes that operational efficiency plays a major role in determining bank profitability, whereas credit risk does not significantly affect ROA during the study period.